An Unusual Cause of Flexor Tenosynovitis: Streptococcus mitis - Bingol, Ugur Anil (Plast Reconstr Surg Glob Open, 2015)
SUMMARY: Streptococcus mitis is a commensal organism of the human oropharynx that rarely causes infection in healthy individuals. Herein, we describe a previously healthy 35-year-old woman who presented with acute pyogenic flexor tenosynovitis of the left index finger due to S. mitis infection. The patient’s infection was treated successfully via surgical and medical interventions, and during follow-up, it was determined that she was complement component C3 deficient. Tenosynovitis is an emergent clinical syndrome that can result in permanent disability or amputation. To the best of our knowledge, this case report is the first to describe tenosynovitis due to S. mitis; in addition, it highlights the importance of initiating therapy with antibiotics that are effective against this rare pathogen.